(untitled) (Journal of Comparative & International Higher Education, 2024)
We are two women international students from the Global South, situated in Turkey and the U.S. respectively. In this article, we utilized collaborative autoethnography to critically reflect on our intellectual, emotional, linguistic, and cultural growth during a virtual exchange program that we participated in during the COVID-19 pandemic. Through this co-exploration, we analyzed our experiences and reflections as participants in a COIL program to consider, more broadly, the evolution and trajectory of virtual mobility in an uneven higher education landscape. Our virtual exchange emerged as a digital and transnational third space, unbounded by hegemonic epistemic, linguistic, or geographical borders. We learned about the vibrant and thriving cultural traditions, thought traditions, and religious/spiritual traditions of Turkmenistan and India, our home countries. Through technologies such as Zoom and WhatsApp, we discovered each other’s personalities and backgrounds, centering sisterhood and friendship along the way. We framed our analysis through a critical internationalization perspective, delineating the challenges and limitations of normative virtual exchanges and arguing for transformative exchanges that honor and affirm the epistemologies of the Global South.